2009
DOI: 10.1016/j.jana.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-Help Groups Can Improve Utilization of Postnatal Care by HIV-Infected Mothers

Abstract: HIV prevention within maternal-child health services has increased in many developing countries, but many HIV-infected women in developing countries still receive insufficient postnatal care. This study explored the experience of 30 HIV-infected women in Vietnam in accessing HIV-related postnatal care, the role of felt and enacted stigma in accessing services, and the effects of participation in a self-help group on utilization of available services. Many HIV-infected women were not provided with adequate info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
74
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 17 publications
5
74
0
1
Order By: Relevance
“…With regard to program exposure and subsequent outcome, our study showed consistent findings with the literature available [23] [28]. FSWs associated with SHGs had increasingly heard about health camps, accessed DIC, and heard of Anti-Retroviral Therapy (ART) in significant numbers.…”
Section: Discussionsupporting
confidence: 83%
“…With regard to program exposure and subsequent outcome, our study showed consistent findings with the literature available [23] [28]. FSWs associated with SHGs had increasingly heard about health camps, accessed DIC, and heard of Anti-Retroviral Therapy (ART) in significant numbers.…”
Section: Discussionsupporting
confidence: 83%
“…They also try to improve their situation by adapting others' experiences with theirs concerning future. On the other hand, sense of being accepted by the group members itself raises self-transcendence among patients (32). In the present study, a significant direct relationship was observed between increased self-transcendence and physical performance.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, members' positive experiences and their shared experiences are obtained with no training. They also learn how to get information and show sympathy to others (32), which information exchange and adaptation skills takes place in the group (33). Our results showed a significant difference between selftranscendence score of both intervention and control groups at the end of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Patients find out their situation, will notice other's welfare by communication with others, and would share their experiences by adapting others' experiences with their own experience and concern about the future and also they will improve their situation. On the other hand, finding an acceptable feeling by other group members would improve self-transcendence in patients (Nguyen et al, 2009). …”
Section: Discussionmentioning
confidence: 99%